2011
DOI: 10.2975/35.2.2011.125.132
|View full text |Cite
|
Sign up to set email alerts
|

A place to be: The role of clubhouses in facilitating social support.

Abstract: It appears that the clubhouse provides an intentional environment that creates a sense of community and a place to belong. The clubhouse as a place to be where one can meet individuals in like situations has been identified as very helpful in achieving recovery by providing the opportunity to rebuild one's shattered social network and offering contact with others in similar contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 34 publications
(38 reference statements)
5
44
0
Order By: Relevance
“…These findings are consistent with the study of Carolan, Onaga, Pernice-Duca, and Jimenez (2011), who revealed from personal narratives that staff, members, and the overall clubhouse structure emerged as the center of social interaction and comfort for participants and a central sustaining means of social support. Furthermore, the results of this study are supported by the earlier investigations of social network support and recovery from mental illness in community (Kim, 2006;Kim et al, 2003).…”
Section: Having a Haven-like Hometownsupporting
confidence: 93%
“…These findings are consistent with the study of Carolan, Onaga, Pernice-Duca, and Jimenez (2011), who revealed from personal narratives that staff, members, and the overall clubhouse structure emerged as the center of social interaction and comfort for participants and a central sustaining means of social support. Furthermore, the results of this study are supported by the earlier investigations of social network support and recovery from mental illness in community (Kim, 2006;Kim et al, 2003).…”
Section: Having a Haven-like Hometownsupporting
confidence: 93%
“…Several studies have explored aspects of social networks among clubhouse members (Biegel, Pernice-Duca, Chang, Chung, Min, & D'Angelo, 2013;Carolan et al, 2011;Pernice-Duca & Onaga, 2009;Pernice-Duca, 2008). Pernice-Duca (2008) and Beigel et al (2013) found that although clubhouse staff and peers made up a substantial portion of the social network, family members were the most nominated source of support.…”
Section: Social Network Among Users Of Clubhouses and Day Centresmentioning
confidence: 99%
“…Clubhouses constitute another community-based approach to psychosocial rehabilitation and, like DCs, provide opportunities for meaningful daily occupations (Norman, 2006;Tjörnstrand, Bejerholm, & Eklund, 2011). Both approaches have been found to facilitate social interaction (Bejerholm & Eklund, 2004;Carolan, Onaga, Pernice-Duca, & Jimenez, 2011) and participation has been described by both groups of users as creating feelings of inclusion and belonging (Carolan et al, 2011;Tjornstrand, Bejerholm, & Eklund, 2013a). Ascertaining whether one approach to psychosocial rehabilitation is better than others in terms of promoting social interaction generates valuable knowledge; successful programmes can inspire less successful ones.…”
Section: Introductionmentioning
confidence: 99%
“…Clubhouse research has begun to identify such a ''space'' as a community [14][15][16][17] that provides a wealth of mutual social support for recovery [14][15][16][17][18][19][20][21]. Aspects of the clubhouse community support have been described in terms of the overall community support as well as its peer component [22,23].…”
Section: Introductionmentioning
confidence: 99%